Impact of a 12-week open-label placebo treatment on headache days in episodic and chronic migraine: a study protocol for a parallel-group, multicentre, randomised controlled trial - Ulrike Bingel; Charly Gaul; Katharina Schmidt; Julian Kleine-Borgmann; Dagny Holle-Lee (BMJ Open, 2021)
Introduction Migraine is the most common neurological disorder and one of the major causes of years lived with disability. Its treatment (especially of chronic forms) is often challenging and accompanied with adverse effects. Although new therapeutic approaches have recently emerged (eg, calcitonin gene-related peptide antibodies), these are linked to strict prescribing guidelines and therefore limited to only a minority of patients. Recently, randomised controlled trials have demonstrated that open-label placebo treatments can lead to significant and clinically relevant improvements of chronic pain conditions.Methods and analysis This multicentre, randomised controlled clinical trial following a parallel group between-subject design aims to systematically investigate the impact of a 12-week open-label placebo treatment on moderate to severe headache days (primary outcome) in patients with episodic and chronic migraine in addition to treatment as usual. Secondary outcomes comprise the number of migraine days, pain intensity, intake of acute medication, quality of life, disability, global impression of change, tolerability and a responder rate. To systematically address potential predictors of placebo responses in patients with migraine, this study assesses potential psychometric predictors, salivary cortisol and alpha-amylase awakening responses, catechol-o-methyltransferase Val158Met polymorphisms, as well as functional and structural brain connectivity (ie, resting state functional MRI, diffusion tensor imaging). The data analysis will be performed on basis of the general linear model considering repeated measures (mixed model).Ethics and dissemination This protocol and all corresponding documents were approved with regard to their content and compliance with ethical regulations by the Ethics Committee of the Medical Faculty of the University Duisburg-Essen, Germany and the Ethics Committee of the Landesärztekammer Hessen. The results from this study will be actively disseminated through manuscript publications and conference presentations.Trial registration number German Clinical Trials Register (DRKS00021259).